Variations of Balinese Verbal Clauses in the Folk Tale I Rare Angon by I Nengah Tinggen - Ni Luh Putu Indah Wahyuni (Dinasti International Journal of Education Management And Social Science, 2025)
This research explores the types and patterns of verbal clause constructions in Balinese folk tales, focusing on Satua I Rare Angon. A satua is a traditional narrative originating from oral traditions, later documented in written form. Verbal clauses, characterized by verbs as predicates, appear in various forms, including active, passive, reflexive, and reciprocal clauses. Satua I Rare Angon was chosen as it predominantly illustrates the actions and reactions of its characters, often aimed at specific goals or prompted by particular events. The story contains social criticism, highlighting issues such as the abuse of power by leaders, exemplified through the character Ida Anake Agung. This study aims to describe the variations of verbal clauses in the narrative using a syntactic approach, analyzing how these constructions contribute to shaping meaning and delivering messages of social critique to the audience. Data collection involves a literature review, supplemented by reading, observing, and noting techniques, followed by qualitative analysis. Findings are presented through formal and informal methods, adhering to the Enhanced Indonesian Spelling System. This research seeks to provide insights into verbal clause roles in Balinese oral literature while deepening understanding of how syntactic structures convey cultural values and critical messages.